Strategies to manage hepatitis C virus (HCV) disease burden. (May 2014) - Wedemeyer, H.; Duberg, A. S.; Buti, M.; Rosenberg, W. M.; Frankova, S.; Esmat, G.; Örmeci, N.; Van Vlierberghe, H.; Gschwantler, M.; Akarca, U.; Aleman, S.; Balık, İ. and Berg, T. and Bihl, F. and Bilodeau, M. and Blasco, A. J. and Brandão Mello, C. E. and Bruggmann, P. and Calinas, F. and Calleja, J. L. and Cheinquer, H. and Christensen, P. B. and Clausen, M. and Coelho, H. S. M. and Cornberg, M. and Cramp, M. E. and Dore, G. J. and Doss, W. and El‐Sayed, M. H. and Ergör, G. and Estes, C. and Falconer, K. and Félix, J. and Ferraz, M. L. G. and Ferreira, P. R. and García‐Samaniego, J. and Gerstoft, J. and Giria, J. A. and Gonçales, F. L. and Guimarães Pessôa, M. and Hézode, C. and Hindman, S. J. and Hofer, H. and Husa, P. and Idilman, R. and Kåberg, M. and Kaita, K. D. E. and Kautz, A. and Kaymakoglu, S. and Krajden, M. and Krarup, H. and Laleman, W. and Lavanchy, D. and Lázaro, P. and Marinho, R. T. and Marotta, P. and Mauss, S. and Mendes Correa, M. C. and Moreno, C. and Müllhaupt, B. and Myers, R. P. and Nemecek, V. and Øvrehus, A. L. H. and Parkes, J. and Peltekian, K. M. and Ramji, A. and Razavi, H. and Reis, N. and Roberts, S. K. and Roudot‐Thoraval, F. and Ryder, S. D. and Sarmento‐Castro, R. and Sarrazin, C. and Semela, D. and Sherman, M. and Shiha, G. E. and Sperl, J. and Stärkel, P. and Stauber, R. E. and Thompson, A. J. and Urbanek, P. and Van Damme, P. and van Thiel, I. and Vandijck, D. and Vogel, W. and Waked, I. and Weis, N. and Wiegand, J. and Yosry, A. and Zekry, A. and Negro, F. and Sievert, W. and Gower, E.
Summary: The number of hepatitis C virus (HCV) infections is projected to decline while those with advanced liver disease will increase. A modeling approach was used to forecast two treatment scenarios: (i) the impact of increased treatment efficacy while keeping the number of treated patients constant and (ii) increasing efficacy and treatment rate. This analysis suggests that successful diagnosis and treatment of a small proportion of patients can contribute significantly to the reduction of disease burden in the countries studied. The largest reduction in HCV‐related morbidity and mortality occurs when increased treatment is combined with higher efficacy therapies, generally in combination with increased diagnosis. With a treatment rate of approximately 10%, this analysis suggests it is possible to achieve elimination of HCV (defined as a >90% decline in total infections by 2030). However, for most countries presented, this will require a 3–5 fold increase in diagnosis and/or treatment. Thus, building the public health and clinical provider capacity for improved diagnosis and treatment will be critical.